Program Pojok Pengrajin Cerdas pada Produk Kerajinan Anyaman Hata di Desa Bojong Pangandaran - Azi Ilham Anshori Azi; Alfi Fahimiah (Jurnal Pemberdayaan Masyarakat, 2024)
Local creative products have considerable potential to be developed, one of which is woven hata, a typical product from Bojong Village, Citumang, Parigi District, Pangandaran Regency, West Java. However, apart from that, conditions in society are quite difficult to connect with each other in optimizing and utilizing the available natural resources and human resources. This research aims to provide a bridge in helping to optimize and utilize the potential of woven hata as a local superior product. This research uses the Participatory Action Research (PAR) method approach as an effort to ensure the success of the program is collaborative, practical, and the community actively participates in its implementation. Implementation of the program was carried out at the Smart Craftsmen's Corner where Mr Misman's PHMS Citumang woven hats were produced, for 16 meetings from June - November 2023, once or twice a week. The results of this research increased the level of knowledge, skills and creativity of the target community group in Bojong Village through the smart craftsmen's corner program by providing structured mentoring, training and hata weaving workshops.